The Oxford handbook of entrepreneurship and collaboration - Reuer, J. J. (Jeffrey J.); Matusik, Sharon F.; Jones, Jessica (New York : Oxford University Press, 2019)
Organisational collaboration has played an important role in the field of strategic management in the last couple of decades. Though the importance of collaboration to entrepreneurship might seem apparent, research on it is distributed across multiple contexts, theoretical perspectives, and units of analysis. The aim of this volume is to highlight this diversity and emphasise the important roles that collaboration plays in value creation, resource acquisition, and the development of entrepreneurial ventures. Interorganisational collaboration involves two or more independent organisations working together under an incomplete contract to accomplish certain objectives. These collaborations might take many forms, ranging from relatively informal or narrow-scope exchanges to equity partnerships.
Inter-Organizational Collaboration and Start-Up Innovation / Vikas Aggarwal, Andy Wu -- Collaboration and Intellectual Property: Strategies for Navigating Fragmented Property Rights / Michael B. Heeley, David R. King -- The Role of Heuristics in Alliance Collaboration for Entrepreneurial Firms / William Hesterly, Jenny Su Bing Smith -- Avoiding Collaboration Stalemates in Technology Commercialization / Phillip H. Kim, Manuel F. Ramírez, Reddi Kotha -- Collaborating for Innovation: The Role of Organizational Complementarities / Peter G. Klein, Mark D. Packard, Karen Schnatterly -- The Communicative Constitution of Entrepreneurship / Timothy Kuhn, Dana Marshall -- Collaborating with Larger Partners: Benefits and Risks for Entrepreneurial Firms / Christian Lechner, Birthe Soppe, Karolina Heggli -- Why Do Small Firms Benefit Less from Alliances than Large Firms? / Michael J. Leiblein, Jeffrey T. Macher, Tiberiu S. Ungureanu -- Types of Spin-Out Firms and Collaborations with Parent Organizations / Vilma Chila, Xavier Martin -- An Intentions-Based Model of Entrepreneurs' Prosocial Behavior: Why Entrepreneurs May Be Exceptionally Generous / Robert A. Baron, Keith M. Hmieleski -- The Crowdfunding Paradigm: An Exploration of Founder-Funder Dynamics and Their Implications for Capability Development and Long Term Success / Sharon F. Matusik, Jessica Jones -- Coordination Frictions in Venture Capital Syndicates / Ramana Nanda, Matthew Rhodes-Kropf -- Collaborative Market Making: The Critical Role of Dyadic and Multi-Partner Alliances in the Formation of New Markets / Pinar Ozcan, Kerem Gurses -- The Effects of Venture Capital Firms on Entrepreneurial Firms' Strategic Alliances and Liquidity Events / Roberto Ragozzino -- Microfoundations of Collaboration in Entrepreneurship / Carlo Salvato -- The Paradox of Control Through Collaboration in Effectual Entrepreneurship / Saras Sarasvathy, Nicholas Dew -- Community
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 6, 2019).
Keywords: Entrepreneurship; Cooperation